MENDETEKSI KECURANGAN DALAM LAPORAN KEUANGAN - Angzeneger, Angzeneger; Nicken Destriana (E-Jurnal Akuntansi TSM, 2023)
This research is a study on Fraudulent Financial Statements. This study aims to obtain empirical evidence regarding the effect of financial stability, leverage, individual financial needs, financial targets, nature of the industry, the ineffectiveness of supervision, auditor turnover, rationalization, audit opinion, capability, size, and liquidity on fraudulent financial statements. The population used is a manufacturing company listed on the Indonesia Stock Exchange for 2017 to 2021 with certain criteria. 58 companies were selected as samples using the purposive sampling method. The samples were processed and tested using multiple regression methods. The results of this study indicate that leverage, individual financial needs, financial targets, the ineffectiveness of supervision, auditor turnover, audit opinion, capability, size, and liquidity do not have an insignificant effect on financial reporting fraud. In contrast, for financial stability, the nature of the industry, and rationalization influence fraudulent financial statements.